The state of our union: prison, politics, and performance within a fragile democracy (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
From September to December of 2017, four University of Michigan students trained by the Prison Creative Arts Project facilitated a creative writing workshop at G. Ronald Cotton Correctional Facility in Jackson, Michigan, USA. Twelve incarcerated men joined the four student facilitators for weekly workshop meetings which culminated in a performance of original creative writing. This article describes the workshop framework and training provided by the Prison Creative Arts Project, introduces the individuals participating in this particular, fall 2017 creative writing workshop, and describes how their creative processes evolved to include political discourse and critique. In conclusion, the article demonstrates how creative writing and theater provide the incarcerated population with the unique opportunity to fully express political opinions and attitudes within prison walls, and highlights parallels between the current events and politics of 2017 and those of 2020. In order to complete this article, the student facilitators wrote a letter describing the project and asking for interest in co-authorship and mailed it to the incarcerated participants. The student facilitators then compiled a questionnaire and mailed it to the incarcerated participants who were interested in co-authoring the article. The co-authors still residing in prison continued to correspond to those living outside of prison via mail, producing sections of the article and providing original writing from the 2017 workshop.
Keywords: Creative writing; Incarceration; Prison; Politics; Performance